Beneficiamento na qualidade física e fisiológica de sementes de capim-mombaça - Melo, Lilian Faria De; Martins, Cibele Chalita; Silva, Givanildo Zildo Da; Boneti, João Eduardo Brandão; Vieira, Roberval Daiton (Universidade Federal do Ceará, 2016)
ABSTRACT Seeds received by forage-grass companies after harvesting contain impurities which are removed by processing machines. This procedure is necessary to obtain seeds which are within the standards of quality for marketing and sowing. The aim of this work was to evaluate the effects of the processing stages on the physical and physiological quality of seeds of guinea grass cv. Mombasa (Panicum maximum), with a view to marketing. Seeds were sampled before processing and after leaving the air screen machine (output from the upper, intermediate and bottom screens), first gravity table (drift, upper and intermediate output), treating machine, and second gravity table (upper, intermediate, and lower output). The seeds were evaluated for water content, physical quality (purity and thousand-seed weight) and physiological quality (germination, first count, classification of seedling vigour, accelerated ageing, seedling length, seedling emergence in the field, and speed of emergence index). Seed processing in the air and screen machine and the gravity table is efficient in improving the physical and physiological quality of the lots of P. maximum cv. Mombasa seed. For this species, processing is necessary to meet the demands for purity and germination established by the Brazilian standards for seed marketing.

RESUMO A semente recebida pelas empresas de gramíneas forrageiras, após a colheita, contém impurezas cuja remoção é realizada por máquinas de beneficiamento. Este procedimento é necessário para a obtenção de sementes dentro dos padrões de qualidade para a comercialização e a semeadura. O objetivo deste trabalho foi avaliar o efeito das etapas de beneficiamento na qualidade física e fisiológica de sementes de Panicum maximum cv. Mombaça, visando à comercialização. As sementes foram amostradas antes do processamento e após a saída da máquina de ventilador e peneiras (descarga das peneiras superior, intermediária e fundo), primeira mesa gravitacional (deriva, descarga superior e intermediária), máquina tratadora e segunda mesa gravitacional (descarga superior, intermediária e inferior). As sementes foram avaliadas quanto ao teor de água, qualidade física (pureza e peso de mil sementes) e fisiológica (germinação, primeira contagem, classificação do vigor de plântulas, envelhecimento acelerado, comprimento de plântulas, emergência de plântulas em campo e índice de velocidade de emergência). O beneficiamento de sementes, na máquina de ar e peneiras e mesa gravitacional é eficiente para o aprimoramento da qualidade física e fisiológica do lote de sementes de P. maximum cv. Mombaça. Para esta espécie o beneficiamento é necessário para atender os requisitos de pureza e germinação estabelecidos pelos padrões de comercialização nacional de sementes.
Processing on the physical and physiological quality of seeds of Guinea grass
Keywords: Panicum maximum; Germination; Vigour; Processing; Purity; Forrage grasses; Panicum maximum; Germinação; Vigor; Processamento; Pureza; Gramíneas forrageiras